Modelagem de transformadores de potência para estudos no domínio da frequência. - Novais, Isabela França (2019)
Power transformers are fundamental to the operation of electric power systems, especially in power transmission and distribution. As they are located between the sources of energy and the final consumption, all the current demanded goes through this component. Thus, together with the lines / cables, the power transformers represent a significant portion of the power losses in this path. The mathematical models currently used in the load flow and harmonic flow studies use single-phase equivalents and don’t consider the contribution of the magnetization branch. This characteristic impairs the loss studies; makes unbalanced studies unfeasible, and also doesn’t allow flow analysis of zero sequence harmonic components. At first, this work presents a three-phase transformer model incorporating the neutral in admittance matrices; grounding impedance; different tapes and the magnetizing branch, without considering the non-linearity of the magnetization current. After this analysis, and in order to contribute to the determination of a mathematical process for the determination of nonlinear magnetization current, for different magnetic materials, a study was conducted to obtain the hysteresis loop using the Jiles-Atherton theory, considering the steel grain oriented silicon and non-oriented grain as magnetic materials.